Предмет: Алгебра, автор: rowijdjdj

решите (нужен не только ответ но и само решение)

(2x-3)^2 -(2x+3)^2 =12

Ответы

Автор ответа: olga0olga76
1

Ответ:

х=-0,5

Объяснение:

(2x-3)² -(2x+3)² =12

(2х-3-(2х+3))*(2х-3+(2х+3))=12

(2х-3-2х-3)*(2х-3+2х+3)=12

(0*х-6)*(4х+0)=12

(0-6)*4х=12

-6*4х=12

-24х=12

х=12/(-24)=1/(-2)

х=-0,5

Проверка:

(2x-3)² -(2x+3)²=

=(2*(-0,5)-3)²-(2*(-0,5)+3)²=

=(-1-3)²-(-1+3)²=

=(-4)²-(2)²=16-4=12 решение получено верно

Похожие вопросы
Предмет: Алгебра, автор: 0ученик0